Factors influencing consumers’ online booking intention on hotel rooms / Ermawati Mad Daud @ Ajamain - Mad Daud @ Ajamain, Ermawati (Faculty of Business and Management, 2018)
The new era of advanced information technology through internet has becoming convenience for internet user. Understanding internet as one of the useful platform of information sharing, people are now influenced to spend most of their time using internet especially for purchasing. Within hotel context, online reviews are definitely important as most of leisure travellers tend to evaluate the reviews of the hotels first before they decided to purchase or book the hotel room(s). Moreover, due to the fact that when consumers read online reviews, they are not paying attention only to the review scores but to other factors as well. This paper aims to discover the factors such as perceived price, perceived trust, online reviews and website usability that influence customers‟ booking intentions on online hotels websites or application such as booking.com, Airbnb, Traveloka, Agoda, Hotels.com and etc. Through internet survey, questionnaires will be distributed to the target respondents and the respondents will be selected by using convenience sampling. Statistical Package for the Social Sciences (SPSS) will be employed for data analysis right after data collection.